Individual philanthropy in post-apartheid South Africa : a study of attitudes and approaches - Wescott, Holly Rodgers (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2009.